Faktor-Faktor yang Memengaruhi Kinerja Keuangan Perusahaan Manufaktur Barang Konsumsi di BEI - Maulinda, Emi; Desyana, Gita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study is conducted to analyze the effect of leverage, liquidity, profitability, and company size on the financial performance of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. This study adopts a method with a sample of 120 observations consisting of 30 consumer goods companies licensed by the Indonesia Stock Exchange through purposive sampling. Data processing uses the help of the Eviews version 12 program. The study findings reveal that leverage and liquidity have no influence on financial performance because the significance value is greater than 0.05. This finding indicates that the level of debt and the ability to meet short-term obligations do not directly affect financial performance. In contrast, profitability has a significant positive effect with a significance value of less than 0.05, confirming that increased operational efficiency and profits drive financial performance. Meanwhile, firm size also contributes significantly but with a negative influence on financial performance, indicating that the larger the scale of the firm, the greater the possibility of decreased efficiency in asset management.
Keywords: Leverage; Liquidity; Profitability; Firm Size; Financial Performance